2018
DOI: 10.1021/acsami.8b05358
|View full text |Cite
|
Sign up to set email alerts
|

Gortex-Based Gas Diffusion Electrodes with Unprecedented Resistance to Flooding and Leaking

Abstract: A significant and long-standing problem in electrochemistry has demanded the need for gas diffusion electrodes that are "flood-proof" and "leak-proof" when operated with a liquid electrolyte. The absence of a solution to this problem has, effectively, made it unviable to use gas diffusion electrodes in many electrochemical manufacturing processes, especially as " gas-depolarized" counter electrodes with significantly decreased energy consumption. In this work, Gortex membranes (also known as expanded PTFE or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…For example, Tiwari et al reported a Gortex-based GDE, where metallic mesh was used as the current collector to provide conductivity, while a Gortex membrane was used to provide hydrophobicity and porosity. 13 It is worth noting that our work and most others reported in the literature used commercial GDLs without any pretreatment. Further work in modifying or pretreating GDLs may prove to be useful in understanding or preventing flooding mechanisms.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…For example, Tiwari et al reported a Gortex-based GDE, where metallic mesh was used as the current collector to provide conductivity, while a Gortex membrane was used to provide hydrophobicity and porosity. 13 It is worth noting that our work and most others reported in the literature used commercial GDLs without any pretreatment. Further work in modifying or pretreating GDLs may prove to be useful in understanding or preventing flooding mechanisms.…”
mentioning
confidence: 88%
“…Lastly, continued development of non-carbon GDLs is also encouraged, particularly ones that decouple the traditional requirements for a GDL (conductivity, hydrophobicity, and porosity) but remain functional over larger areas. For example, Tiwari et al reported a Gortex-based GDE, where metallic mesh was used as the current collector to provide conductivity, while a Gortex membrane was used to provide hydrophobicity and porosity . It is worth noting that our work and most others reported in the literature used commercial GDLs without any pretreatment.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…A possible solution is to develop a type of hybrid reactor which have catholyte but no anolyte to study the half-cell potential of the gas-phase-membrane reactor. [170] In addition to the cell geometry, the CO 2 R performance in these cells can be influenced by the catalyst deposition methods, [18] the identity of the binder and ion-exchange membrane, [171] the decoration layer on the catalyst materials, [32] the composition of the GDE and electrolyte pH, [172][173][174] implying that the reaction environments surrounding the catalytic center are crucial for CO 2 R. [161]…”
Section: Influence Of the Reaction Environments On Co 2 Rmentioning
confidence: 99%
“…Therefore, it is crucial to supply sufficient water to the cathode to prevent precipitation . An excess of water will 1) dilute the product, which is undesired for downstream separation purposes, and 2) cause flooding of the GDE, limiting mass transport of CO 2 . Currently, water is supplied to the CO 2 stream by bubbling the gas through a heated water reservoir, resulting in a saturated gas flow .…”
Section: Figurementioning
confidence: 99%